Lubricant And Tribological Properties Of Zinc Compound In Palm Oil - Md Alias, Muhammad Aizat; Abdollah, Mohd Fadzli bin; Amiruddin, Hilmi (Emerald Group Publishing Ltd., 2019)
Purpose: This paper aims to investigate the composition of lubricant and the enhancement of tribological properties using palm oil as a parent base oil mixed with an organo-zinc compound as an additive. Design/methodology/approach: The oil samples were prepared by mixing organo-zinc compound additive, zinc dioctyldithiophosphate (ZnDoDP) and zinc diamyldithiocarbamate (ZDDC), at 0 to 3.0 Wt.% concentrations with commercialised palm oil which were then homogenised using an ultrasonic homogeniser. The oil samples were then tested for their oil properties through elemental analysis, their viscosity index, flashpoint and acid number. Next, the friction test was performed using a four-ball tribometer, and the worn surfaces of the balls were observed using a digital microscope. Findings: The results showed that commercialised palm oil with 2.0 Wt.% of ZnDoDP had excellent characteristics regarding its lubricant properties, such as its viscosity index, coefficient of friction and wear compared to commercialised palm oil with the addition of 2.0 Wt.% of ZDDC. Originality/value: To the best of the authors’ knowledge, this is the first study to compare the effect of the concentration of ZnDoDP and ZDDC on the lubricant and triological properties of vegetable oil (palm).